Estudo da corrosão de cadinhos de SnO2-ZnO, na fusão de vidros contendo metais pesados - Nascimento, Erlandson Thiago Oliveira; Lima, Ana Paula Kawabe; Varela, José Arana; Longo, Elson; Hernandez, Antonio Carlos; Bertochi, Maria Aparecida Zaghete; Perazolli, Leinig (Eclética Química, 2002)
In this work it was studied resistance of crucibles of SnO2 doped with 1%mol of ZnO when they are submitted to thermal treatment for melting glass with heavy metals. The crucibles were obtained through the slip casting process, and the sintering temperature was 1400ºC by 4 hours. The glass composition of 50B2O3-50PbO, 60B2O3-40BaO and 66,67B2O3-33,33PbO was melted at 700ºC, 1150ºC and 700ºC respectively. All these glasses compositions were melted only one time for 1h and chilled inside the crucibles. These crucibles were analyzed by SEM-EDS.